Touristsâ outbound travel behavior in the aftermath of the COVID-19: role of corporate social responsibility, response effort, and health prevention - Chua, Bee Lia; Al- Ansi, Amr; Lee, Myong Jae; Han, Heesup (Taylor and Francis Group, 2021)
Little is known regarding how the tourists will perceive the post-pandemic travel particularly when planning to travel to the most affected global destinations. This study was designed in response to the COVID-19 pandemic and its adverse impact on the travel and tourism industry. It primarily investigated the key factors of the U.S. tourists’ destination attachment and the intentions to return to European and Asian destinations after the pandemic. A total of 367 participants were involved in the web-based survey. The results of the structural equation modeling demonstrated that in the event of a pandemic (1) the corporate social responsibility and the perceived response efforts were critical to generate the destination attachment and the approach behavioral intentions, (2) monetary promotions were not sufficient to generate the destination attachment and approach the behavioral intentions to the international destinations, and (3) the health preventive behavior and the destination attachment were important direct predictors of the approach behavioral intentions. These key findings could assist the travel and tourism companies to more effectively overcome the adverse impact of the pandemic on their businesses.